Numerical Method for Evaluating E-Cash Security - Dany Eka Saputra; Sarwono Sutikno; Suhono Harso Supangkat (Universitas Ahmad Dahlan, 2018)
Security evaluations of electronic cash (e-cash) schemes usually produce an abstract result in the form of a logical proof. This paper proposes a new method of security evaluation that produces a quantitative result. The evaluation is done by analyzing the protocol in the scheme using the Markov chain technique. This method calculates the probability of an attack that could be executed perfectly in the scheme’s protocol. As proof of the effectiveness of our evaluation method, we evaluated the security of Chaum’s untraceable electronic cash scheme. The result of our evaluation was compared to the evaluation result from the pi-calculus method. Both methods produced comparable results; and thus, both could be used as alternative methods for evaluating e-cash security.